Industry Dynamics over the Business Cycles - James Bergin; Dan Bernhardt Bernhardt (Queen's University, Department of Economics, 1996)
We develop a theoretical model of the dynamics of an industry over the business cycle. In the economy, both aggregate demand and the productivity of a firm's technology evolve stochastically. Each period, firms must choose whether to produce or to exit and attempt to sell off their resources to an entrant, so there is a non-trivial opportunity cost of production. We characterize the intertemporal evolution of the distribution of firms, where are distinguished by their capital in place and the productivity of their technology. We characterize exit rates by age, size and productivity. A useful social planner's characterization of the competitive equilibrium is provided. Predictions of our theoretical model are broadly consistent with observed cyclical patterns.
Keywords: E32; L16; 330; stochastic heterogencity; aggregate shocks; social planner; exit; capital in place; thin markets